Analisis Strategi Promosi dalam Meningkatkan Keunggulan Tadika Mysarah - Anisah Siregar; Alfi Amalia (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research aims to find out how promotional strategies are used to increase the excellence of Tadika Mysarah. Tadika Mysarah as a preschool educational institution, needs to have an effective promotional strategy to be able to attract the interest of parents and maintain a positive image despsite the large amount of competition. The research method used is qualitative descriptive analysis, with data collection through interviews, observation and documentation. This research focuses on the forms of promotion carried out, such as digital marketing through social media, direct promotion through open days and brochures. The research results show that social media-based promotional strategies via Facebook and Instagram are an important element in strengthening and reaching a wider target audience. Apart from that, promotional programs involving activities, such as competitions and parent meetings, contribute to increasing public trust. Personal communication strategies with parents and providing quality services also strengthen customer loyalty.